2011
DOI: 10.1007/s11999-010-1609-9
|View full text |Cite
|
Sign up to set email alerts
|

How to Treat A Tibial Post Fracture in Total Knee Arthroplasty?

Abstract: Background Posterior-stabilized TKAs, which use a polyethylene tibial post to articulate against a metal femoral cam, are used regularly. Reported complications are related to the patellofemoral articulation or the tibial postcam mechanism. Fracture of the tibial post is an uncommon but disabling complication after posterior-stabilized TKA that requires operative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 32 publications
1
30
0
2
Order By: Relevance
“…Tibial post damage in TKA remains an important issue [26] with the incidence of failure resulting from post fractures estimated at approximately 1% [17] but recorded as high as 12% in one implant series [2]. One recent study of three contemporary inserts established that tibial post damage was primarily determined by the insert design and to a lesser extent the duration of implantation and revision diagnosis [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tibial post damage in TKA remains an important issue [26] with the incidence of failure resulting from post fractures estimated at approximately 1% [17] but recorded as high as 12% in one implant series [2]. One recent study of three contemporary inserts established that tibial post damage was primarily determined by the insert design and to a lesser extent the duration of implantation and revision diagnosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that the cam-post is not an innocuous articulation [14,26]. Tibial post wear is a major factor in the production of osteolytic polyethylene particles and can ultimately lead to catastrophic failure including post fractures [1,2,4,10,[17][18][19]26]. The creation of a high flexion tibial insert design was introduced with the intent of allowing deeper flexion, particularly in patients with high preoperative flexion.…”
Section: Introductionmentioning
confidence: 99%
“…Articular surface post width, thickness, and shape were similar between designs. To simulate observed clinical results, no accelerated aging was performed: it has been shown that many post fractures occur soon after surgery, prior to significant oxidation.…”
Section: Methodsmentioning
confidence: 99%
“…Fracture of the articular surface tibial post is rare but a potential complication of posterior‐stabilized (PS) and constrained condylar knee (CCK) total knee replacements (TKR). PS post fractures in most systems present at a rate between 0.05% and 1%, often between 2 months to 3 years after implantation but have been reported to occur at a rate of up to 12.4% (in a specific design) . The cause of articular surface tibial post fracture appears to be due to two distinct loading conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation